Meningkatkan Ketrampilan Berpikir Kritis Menggunakan Bimbingan Konseling Kelompok Teknik Problem Solving Berbantuan Mind Mapping - M. Zuhdi Zainul Majdi; Desti Ekawati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2020)
The purpose of this study was to test the effectiveness of group guidance on mind mapping and problem solving techniques to improve students' critical thinking skills in mathematics. This study used a random control group pretest-posttest design, involving 14 students of SMKN 3 Sukabumi. The data analysis technique used is one-way Anova. The results showed that the group guidance of mind mapping and problem solving techniques was effective in improving students' critical thinking skills in mathematics. Through this research, it is expected to be able to provide understanding to students that it is important to have critical thinking skills because students have developmental tasks that must be achieved in order to develop optimally with regard to mathematics subjects to be more responsible and consequently.